Unravelling Conspiracy Theory Within Cultural Semiotics Framework as Narrative and Communication Strategies in Indonesian Social Media - Fadilah, Eka (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
This paper aimed at exploring the meaning-making processes of conspiracy theories echoed by social media influencers as strategic narrative and communication systems. The topic was grounded in a cultural semiotic approach to dissect the aspects of signifier and signified as construed in social media. A nexus-case study was applied to make a deep analysis of meaning-making construction produced and re-produced by the influencers, taking up data triangulation derived from social media, theoretical frameworks, and empirical investigations. The study revealed that meaning was constructed through manipulating signifiers like Covid-19, Lato-Latto, and Dajjal worshipping, which were related to other floating signifiers to create polarization from the audience's perspective. Further, the meaning-making process was ontologically and epistemically baseless. Advanced recommendations are reiterated through this paper to provide a wide range of insight to cope with the issue presented.